ANALISIS PENGARUH PENGATURAN DAYA REAKTIF UNTUK FILTER HARMONIC TERHADAP PERUBAHAN THDi PADA SISTEM TENAGA LISTRIK - Rinas, I Wayan; Maharta Pemayun, A. A Gede; Suartika, I Made (Jurnal SPEKTRUM, 2020)
Harmonic filters are used to reduce harmonic distortion in electric power systems. In active filters, usually the required reactive power (Qc) can be adjusted. In this study, an analysis of the Qc setting on the Active filter was carried out to determine the effectiveness of the filter so that the THDi (total harmonic distortion) was obtained which was in accordance with the IEEE 519-2014 standard (8%). The results of the analysis of the smallest Qc which can still reduce harmonic distortion when meeting the IEEE 519-2014 standard is Qc 55% of the maximum reactive power with THDi for pasa R = 7.38%; S = 7.81%; and T = 5.94%. Control is needed to adjust the Qc on the filter, because the Qc value will continue to change according to the electric load being operated.